Estágio em educação ambiental na Fubá Educação Ambiental - Pompilio, Geovanna Dela Ricci Maronesi (Universidade Federal de São Carlos, 2023)
The Projeto Pedagógico do Curso de Bacharelado em Gestão e Análise Ambiental da Universidade Federal de São Carlos profess that the Final Course Project may constitute a professional Internship. Therefore, the objective of this internship was to get to know the dimensions, principles and tools of critical, dialogical and inclusive environmental education and monitor its practical application, in addition to planning and monitoring environmental education activities, mainly aimed at biodiversity conservation, at the company Cornmeal Environmental Education (São Carlos - SP).
Internship in environmental education at Fubá Educação Ambiental
Keywords: Educação; Conteúdo para aplicativo; Cursos educativos; Education; Content for app; Educational courses; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO